Biomechanical properties of Bovine tendon xenografts treated with a modern processing method - Colaco,H; Lord,BR; Back,DL; Davies,AJ; Amis,AA; Ajuied,A (Journal of Biomechanics, 2017)
Xenograft tendons have been used in few human studies, with variable results. With the advent of novel tissue processing techniques, which may mitigate against an immune-mediated rejection response without adversely affecting mechanical properties, there maynowbe a clinical role for xenograft tendons, particularly in knee ligament reconstruction. We hypothesize that‘BioCleanse®’processed bovine extensor digitorum medialis(EDM) tendons exhibit favorable time-zero pre-implantation biomechanical characteristics when compared to both unprocessed bovine EDM tendons and BioCleanse® processed human cadaveric allograft tibialis anterior tendons.In this in vitrocase controlled laboratory study, three groups of tendons underwent a 5-stage static loading test protocol: 15 BioCleanse® bovine (BCB), 15 fresh frozen unprocessed bovine (FFB), and 12 BioCleanse® human allograft (BCA) tendons. Cross-sectional area of the grafts was measured using an alginate molding technique, and tendons were mounted within an Instron® 5565 Materials Testing System using cryogenic clamps. BCB tendons displayed a higher ultimate tensile stress (p<0.05), with equivalent ultimate failure load, creep, and modulus of elasticity when compared to the FFB tendons (p>0.05). BCB tendons had an equivalent cross-sectional area to the BCA tendons (p>0.05) whilst exhibiting a greater failure load, ultimate tensile stress, less creep and a higher modulus of elasticity (p<0.05).The BioCleanse® process didnot adversely affect the time-zero biomechanical roperties of bovine xenograft EDM tendons. BioCleanse® processed bovine xenograft EDM tendons exhibitedsuperior biomechanical characteristics when 3compared with BioCleanse® processed allograft tibialis anterior tendons